The Impact of a Breast Cancer Diagnosis on the Social Interaction Patterns of Young Omani Women: A Qualitative Study Approach - Mohammed Al-Azri; Zayana AL-Kiyumi; Khalid Al-Bimani; Huda Al-Awaisi (Current Oncology)
Background and Aim: Young women diagnosed with breast cancer (BC) face considerable psychological and emotional distress, impacting their interactions with themselves, their families, and the wider community. This study sought to explore the interaction patterns of young Omani BC survivors following their diagnosis and during treatment. Materials and Methods: Semi-structured individual interviews were conducted with 11 Omani women diagnosed with BC, recruited from the Sultan Qaboos Comprehensive Cancer Care and Research Centre in Muscat, Oman. Participants were selected using purposive sampling to target Omani BC survivors aged under 45 years, with one to five years of survivorship post-diagnosis. Framework analysis was employed to analyse the qualitative data. Results: Six key types of interactions with various groups were identified: self, children, spouses, family, friends, and society. While many BC survivors demonstrated resilience through their strong faith, viewing the illness as part of a divine plan, others experienced diminished confidence and social withdrawal due to body image issues. Interactions with children centred on maintaining normalcy, while spouses typically provided emotional support despite challenges with intimacy. Family and friends offered crucial support, although concerns regarding societal stigma led some women to conceal their diagnosis. Conclusions: Participants in this study demonstrated a strong sense of acceptance of their cancer diagnosis as a result of their faith, viewing it as part of a divine plan. Their belief in divine guidance, paired with optimism about the available treatments, fostered resilience, allowing them to maintain a calm and hopeful outlook during their journey of treatment and recovery. However, some participants experienced a decline in self-confidence, particularly after treatment. This affected their willingness to socialise and interact with others, leading to introversion and a marked withdrawal from social interactions, often related to changed self-perception or fear of judgment following changes in appearance.